Revisiting Covid-19: The Novel Disease That Shattered the World - Jain, Rohit; Agarwal, Dilip (Asian Journal of Pharmaceutical Research and Development, 2020)
COVID-19 is a highly contagious disease which is caused by SARS-CoV-2. The disease was initially originated from Wuhan in China. SARS-CoV-2 has a similarity with the SARS-CoV virus and MERS virus. However, the fatality rate in infection caused due to SARS-CoV-2 is less as compared to the infection caused by SARS-CoV and MERS virus. Initially, the WHO had declared the disease as Public Health Emergency of International Concern, and later the disease was categorized as pandemic disease. The disease had affected more than 200 countries. The USA tops the list with the highest number of infected patients. The ACE is the primary receptor of this virus, and the transmission is through both direct and indirect contact. The disease is diagnosed through the reverse-transcription polymerase chain reaction and complimented with a chest computed tomography scan. There is no specific treatment of COVID-19, and supportive management is recommended in severe cases.